Hovorové spisovné projevy v mluvených médiích - Štěpán, Josef (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2017)
The article deals theoretically with colloquial standard discourses in media. It adduces examples of colloquial standard means on the individual levels of the language system. The production of colloquial standard texts, in which naturalness together with responsibility of the speaker play an important role, is generally described. This production is characterised in a complicated situation of spoken media. „Good speech models”, necessary after restoration of social elites after 1989, are important in media for the broad strata of population and should become a subject of linguistic research more often.
Keywords: colloquial standard discourses; common Czech; everyday language; naturalness; responsibility; spoken media